Implementasi Manajemen Kurikulum pada Madrasah Diniyah Sirojut Tholibin Tamansari Pamekasan, Madura - Yustiani S (Analisa: Journal of Social Science and Religion, 2009)
Madrasah Diniyah Sirojut Tholibin Pondok Pesantren Tamansari in performinglearning process refer to Religion Department’s curriculum and curriculum arrangedby this Pondok Pesantren. The Madrasah implemented curriculum managementcovering several procesess, namely planning, organizing, learning process, supervision,monitoring, and evaluation. In implmenting the curriculum, there are severalsupporting and obstracting factors. Supporting factors include teachers, silaturahmiforum, madrasah exercise laboratory, and muhafadoh team. And obstracting factorsare limited educational facilities.Key Words: Implementation, Management, Curriculum